SOCIAL CONDITIONS OF SUSTAINABLE TOURISM DEVELOPMENT – CASE OF RESIDENTS OF POZNAŃ - Agnieszka Niezgoda (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article presents social conditions of sustainable tourism development in case of residents of Poznań. Local communities play a decisive role in the development of tourism at the place of their residence. Local people have an impact on the shape of the tourism product not only through providing their labour, specifically in the tourism sector, but also by creating the general “atmosphere of a place”, which may become a factor in the perception of the place as an attractive tourism destination. The article presents the results of primary empirical research conducted in 2009 among residents of Poznań. The aim was to learn the residents’ attitudes to tourists (now and in the future) and perception of positive and negative results of tourism development. The survey have shown, that residents of Poznań accept tourists and see the role of tourism in the city development.